PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN KEBIJAKAN DIVIDEN TERHADAP KUALITAS LABA - Manalu, Sinta Claudia; Armeliza, Diah; Prihatni, Rida (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
The purpose of this research is to test whether there is an effect of profitability, liquidity, leverage, and dividend policy on earnings quality. The population that is the subject of this study are companies in the primary consumer goods sector that are listed on the Indonesian Stock Exchange (IDX) in the period 2019 to 2022. The number of samples in this study were 42 companies with a total of 168 observations. The sampling technique used purposive sampling method. In this study used quantitative methods with data sources obtained from secondary data. The data analysis used was panel data regression analysis using Eviews version 12. The results of this study show empirical evidence that, although the liquidity variable has a positive effect on earnings quality, the profitability variable has a negative effect. However, leverage and dividend policy variables do not affect earnings quality significantly; conversely, the variable profitability, liquidity, leverage, and dividend policy simultaneously affect the quality of significant earnings.